Oxidative stress in aging - Vina, Jose (Henry Stewart Talks, 2007)
Characteristics of aging, The decay of aging: cellular, tissue and organism level, The longevity curves: maximum and average life span, The theories of aging, The free radical theory of aging, Mitochondrial damage, Markers of oxidative stress in aging, Differences in oxidative stress in aging explain the differential longevity between genders, Interventions: antioxidant vitamins, estradiol, regular exercise, caloric restriction, antioxidant enzymes
Archived at 2018/05/31